Obesity and Insulin Resistance in Asthma Pathogenesis and Clinical Outcomes - Sabina Škrgat; Matevž Harlander; Miodrag Janić (Biomedicines, 2024)
Common inflammatory ground links obesity, insulin resistance, and asthma. As recognition of their interplay, one worsening the natural course of the other, is recognised, questions remain about how to adequately address them altogether to improve clinical outcomes. The present manuscript sheds light on the problem, describing possible pathophysiological links, clinical views, and therapeutic challenges, raising questions about what remains to be done, and calling for multidisciplinary treatment of these patients to detect diseases early and adequately address them before they become full-blown and deteriorate their health and quality of life.